DEVELOPMENT OF EFFECTIVE METHODS OF STRENGTHENING DAMAGED WALLS OF BUILDINGS TO BE RECONSTRUCTED (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article presents defects formed during the operation of buildings and structures, in particular, defects of brick walls and their reinforcement in reconstructed buildings.